Pengaruh Gaya Hidup Terhadap Peningkatan Gaya Konsumtif di Kalangan Generasi Z Kota Solo - Dea Ananda; R.Taufiq Nur Muftiyanto; Agus Suyatno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
A wasteful lifestyle makes it difficult for a person to limit excessive or unnecessary spending, this lifestyle leads to excessive spending. According to the Surakarta Book, Solo City has a population in 2023 of around 526,870 people, while Generation Z, which is the focus of this research, has an age range of 15-24, totaling 81,524 people consisting of 41,584 men and 40,040 women. This research uses quantitative data with the number of samples in this study is 100. All data and information for this study were collected from primary sources through questionnaires or questionnaires. Lifestyle has a significant effect on consumptive style with the t test results showing t count of 6,851 with a significant 0.000. It is known that the t value of the variable count is greater than the t table 1.98472 and the significance is less than 0.05. Based on these results, Lifestyle has a positive effect on Consumptive Style.